2016
DOI: 10.1097/wad.0000000000000132
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Profiles on the Severe Impairment Battery Are Similar in Alzheimer Disease and Down Syndrome With Dementia

Abstract: Previous research has revealed similarities in the neuropathology, clinical presentation, and risk factors between persons with Alzheimer’s disease from the general population (GP-AD) and those with Down syndrome (DS-AD). Less is known, however, about the extent of similarities and differences in the cognitive profiles of these two populations. Fifty-one moderate-to-severely demented GP-AD and 59 DS-AD individuals participated in this study which compared the cognitive profiles of these two populations on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…The data from the neuropsychological battery supported the clinicians' observations of transition status. In prior studies, the neuropsychological battery used was found to be correlated with clinical dementia status [54,55]. In this study, the slope of the neuropsychological measures correlated with clinical transition status.…”
Section: Discussionmentioning
confidence: 55%
“…The data from the neuropsychological battery supported the clinicians' observations of transition status. In prior studies, the neuropsychological battery used was found to be correlated with clinical dementia status [54,55]. In this study, the slope of the neuropsychological measures correlated with clinical transition status.…”
Section: Discussionmentioning
confidence: 55%
“…To assess the degree to which the AD and DS subjects were functionally comparable, ratings from a modified version of the Bristol Activities of Daily Living Scale (mBADLS), collected within the last 1–2 years of life, were calculated. The mBADLS does not include items that DS individuals may not have been able to perform early in life (eg, managing finances), and is based on a 0–42 point scoring system with higher scores indicating greater functional dependency (Table ). Higher mBADLS scores have been shown to be associated with lower cognitive scores on the severe impairment battery for AD and DS individuals .…”
Section: Methodsmentioning
confidence: 99%
“…The mBADLS does not include items that DS individuals may not have been able to perform early in life (eg, managing finances), and is based on a 0–42 point scoring system with higher scores indicating greater functional dependency (Table ). Higher mBADLS scores have been shown to be associated with lower cognitive scores on the severe impairment battery for AD and DS individuals . Median mBADLS scores for DS and AD groups were 34.5 and 36, respectively; two AD individuals had comparatively lower scores than the other AD and DS cases.…”
Section: Methodsmentioning
confidence: 99%
“…This indicates that these assessments may not be accurately assessing differences in these groups. Research by Dick, Doran, Phelan, and Lott () found no difference on any of the SIB subscales between people with DS and dementia and typically developing people with the AD when the functional abilities of the two groups were controlled for. The authors suggest that the SIB was not appropriate for use with people with more severe impairment.…”
Section: Cognitive Measuresmentioning
confidence: 99%